Examining adherence to oral anticancer medications through a human factors engineering framework: Protocol for a scoping review. - Irene D Lin; Matthew B Shotts; Ahmad Al-Hader; Kellie Jones Weddle; Richard J Holden; Emily L Mueller; Monica R Macik; Mirian Ramirez; Ephrem Abebe (PLoS ONE)
Background The number of oral anticancer medications has increased over the past few decades, opening new possibilities in cancer care and improving convenience for patients and caregivers. However, adherence levels continue to be suboptimal, potentially jeopardizing therapeutic benefits. Poor adherence levels may indicate gaps in current strategies and interventions aimed at enhancing medication adherence and the extent to which they address the complex and multi-faceted medication management needs of patients and their caregivers. Beyond commonly understood barriers (e.g., forgetting to take medications), adherence interventions must address systemic barriers that may not be fully appreciated by members of the healthcare system. This scoping review aims to apply a systems framework (human factors engineering framework) to examine system elements targeted by adherence enhancing interventions. Methods Studies published in English, reporting adherence interventions for oral anticancer medications with adherence and/or persistence as primary outcome measures will be included in this review. We will search the following electronic databases with no limits on dates: Ovid MEDLINE, Cochrane Library, Web of Science Core Collection, Embase, CINAHL Complete, PsycInfo, and Scopus. Two reviewers will independently screen study titles and abstracts for inclusion with a third reviewer adjudicating conflicts. Full text of included articles will be used to extract information on systemic barriers targeted by adherence interventions as well as information about intervention type, outcomes, and study characteristics. Extracted information will be synthesized to generate a summary of work system factors targeted by adherence interventions. Discussion Through application of a systems-based approach, this scoping review is expected to shed light on the complex and multifaceted nature of factors influencing adherence to oral anticancer agents. The review may also identify areas that are ripe for further research.